دور التصال الصحي عبر شبكات التواصل الاجتماعي في تعزيز الاداء العلاجي لدى المريض - مروة نقاز; د/ عطالله طريف (جامعة عمار ثليجي الاغواط, 2024)
الملخص: جاءت هذه الدراسة بعنوان دور الاتصال الصحي عبر شبكات التواصل الاجتماعي في تعزيز الأداء العلاجي لدى المريض. وهدفت إلى معرفة مدى اعتماد المرضى على شبكات التواصل الاجتماعي في علاج حالاتهم ومتابعتها، والكشف عن كيفية مساهمة شبكات التواصل الاجتماعي في تعزيز الرعاية الصحية لدى المريض. من خلال محأولة الاجابة عن التساؤل الآتي: هل يساهم الاتصال الصحي عبر شبكات التواصل الاجتماعي في تعزيز الأداء العلاجي لدى المريض؟ واعتمدنا في هذه الدراسة على المنهج الوصفي من خلال توزيع استمارة على عينة من مرضى قدر عددهم ب 20 شخص من صنف النساء والرجال بولاية الاغواط على مستوى مستشفى عام . وقد توصلنا إلى النتائج الآتية : أن غالبية المرضى يستخدمون شبكات التواصل الاجتماعي مع تفضيلهم لشبكة الفيسبوك.كما أشارت النتائج بأن هناك اهتمام متزايد بالمحتوى الصحي عبر شبكات التواصل الاجتماعي وذلك لأن غالبيتهم يتابعون صفحات صحية عبرها.كما أن نصف المشاركين يعتمدون على شبكات التواصل للتواصل مع مقدمي الرعاية الصحية لطلب النصائح وطرح الأسئلة وهذا ما يؤكد على فعالية الاتصال الصحي في تعزيز الأداء العلاجي من خلال تسهيل التواصل وتلقي الدعم وتجنب التنقل .رغم وجود بعض التحديات كصعوبة التواصل الشخصي والمباشر مع الطبيب. الكلمات المفتاحية: الاتصال الصحي، شبكات التواصل الاجتماعي، المريض، الأداء العلاجي. Abstract: This study, titled "The Role of Health Communication via Social Media Networks in Enhancing Therapeutic Performance for Patients," aimed to understand the extent to which patients rely on social media networks for treating and monitoring their conditions, and to reveal how social media networks contribute to enhancing healthcare for patients. The study attempted to answer the following question: Does health communication via social media networks contribute to enhancing therapeutic performance for patients? We adopted a descriptive approach in this study by distributing a questionnaire to a sample of 40 patients, including both women and men, in the Laghouat province at two clinics, one public and one private. We reached the following results: The majority of patients use social media networks, with a preference for Facebook. The results also indicated an increasing interest in health content on social media networks, as most patients follow health pages on these platforms. Half of the participants rely on social networks to communicate with healthcare providers to seek advice and ask questions, which confirms the effectiveness of health communication in enhancing therapeutic performance by facilitating communication, receiving support, and avoiding travel. This is despite some challenges, such as the difficulty of personal and direct communication with the doctor. Keywords: Communication, Patients, Health Communication.